Acute metabolic effects of melatonin—A randomized crossover study in healthy young men. Issue 2 (6th December 2020) - Kampmann, Ulla; Lauritzen, Esben S.; Grarup, Niels; Jessen, Niels; Hansen, Torben; Møller, Niels; Støy, Julie
Abstract: Melatonin regulates circadian rhythm, but may also have effects on glucose homeostasis. A common G‐allele in the MTNR1B locus has been associated with an increased risk of type 2 diabetes (T2DM). We aimed to examine acute effects of high doses of melatonin on glucose metabolism with attention to MTNR1B genotype. Twenty men were examined in a double‐blinded, randomized crossover study on two nonconsecutive days with four doses of 10 mg oral melatonin or placebo. Insulin sensitivity and insulin secretion were assessed by an intravenous glucose tolerance test (IVGTT) and a hyperinsulinaemic‐euglycaemic clamp (HEC). Blood samples were drawn to determine the metabolic profile and MTNR1B rs10830963 genotype. Indirect calorimetry and blood pressure measurements were also performed. Insulin sensitivity index was significantly reduced on the melatonin day ( P = .028) in the whole group and in homozygous carriers of the rs10830963 C‐allele ( P = .041). Glucose during the IVGTT was unaffected, but there was a tendency towards lower insulin and C‐peptide levels in the first minutes after glucose administration in G‐allele carriers. Systolic blood pressure decreased and lipid oxidation increased significantly on the melatonin day in rs10830963 G‐allele carriers. Overall, our study reports that acute administration of melatonin in supra‐physiological doses may have a negative impact on insulin sensitivity. Clinical trial registration number (clinicaltrial.gov): NCT03204877.